Ononin Shows Anticancer Activity Against Laryngeal Cancer via the Inhibition of ERK/JNK/p38 Signaling Pathway - Ye, Ben; Ma, Jianhua; Li, Zhaoxia; Li, Yang; Han, Xiaopan (Frontiers in Oncology, 2022)
Background: Laryngeal cancer is a type of head and neck tumor with a poor prognosis and survival rate. The new cases of laryngeal cancer increased rapidly with a higher mortality rate around the world. Objective: The current research work was focused to unveil the in vitro antitumor effects of ononin against the laryngeal cancer Hep-2 cells. Methodology: The cytotoxic effects of ononin against the laryngeal cancer Hep-2 cells and normal HuLa-PC laryngeal cells were studied using an MTT assay. The intracellular ROS generation, apoptotic cell death, MMP, and cell adhesion on the 25 and 50µM of ononin-treated Hep-2 cells were detected using respective staining assays. The levels of TBARS and antioxidants were assayed using specific kits. The expressions of JNK1/2, ERK1/2, p38, PI3K1/2, and Akt in the ononin-treated Hep-2 cells were investigated using RT-PCR assay. Results: The ononin treatment effectively inhibited the Hep-2 cell viability, whereas did not affect the viability of HuLa-PC cells. Furthermore, the ononin treatment effectively improved the intracellular ROS accumulation, depleted the MMP, and triggered apoptosis in Hep-2 cells. The TBARS were improved, and GSH levels and SOD were depleted in the ononin-administered Hep-2 cells. The ononin treatment substantially inhibited the JNK/ERK/p38 axis in the Hep-2 cells. Conclusion: Altogether, the outcomes of this exploration proved that the ononin has remarkable antitumor activity against laryngeal cancer Hep-2 cells.